PENGARUH PENURUNAN TARIF PPH, PELAYANAN PAJAK, SERTA SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Agus Widodo; Hetty Muniroh (STIE Pelita Nusantara Semarang, 2021)
The research that has been conducted aims to determine the effect of lowering income tax rates, tax services, and tax penalties on the compliance of UMKM taxpayers in Rembang Regency. This research was conducted on UMKM respondents in the Rembang Regency with a sample of 104 respondents. The sampling technique uses purposive sampling technique, namely the sample taken meets predetermined criteria. Respondents' data were collected using questionnaires with a Likert scale of 1-5 categories. The quantitative data analysis method used is the classical assumption test, multiple linear analysis, hypothesis testing using the t test and the coefficient of determination (R2). The results of this study indicate that the reduction in income tax rates, tax services, and tax sanctions have a significant effect on the compliance of MSME taxpayers in Rembang Regency. The practical implications of the results of this study can become a reference for further research and as a basis for policy making from interested parties